The analysis of the CFR TRAVELLERS SA activity from the viewpoint of efficiency indicators - SIMA, Elena (Annals of Spiru Haret University. Economic Series, 2010)
The purpose of the paper is to make an analysis of the transport activity at CFR travellers SA based on the evolution of the main efficiency indicators in this field. The purpose of the analysis is to accurately determine the advantages and disadvantages of this activity and to find ways to improve it. We have chosen this activity because it has dropped in intensity during the last years and also because its quality is lacking in Romania. The analysed period is 2007-2009 and graphics have been made to see the indicators’ evolution and to allow the activity’s assessment. The European Union encourages railway transport because of its advantages and because it is probably the most environmentally friendly and it is one way to achieve sustainable transport.